Colour, form, animals and deception in the ice age - Petru, Simona (Documenta Praehistorica, 2008)
Vision is the main sense through which we observe and recognise the outside world. Humans are among the few mammals with trichromatic vision, which is important for food procurement and evading predators. For better hunting success, ice age people camouflaged themselves as animals. It is possible that without such an ability for deception, symbolic thought would never have evolved. Because vision is so important to humans, visual forms of the transmission of information emerged early in the history of modern humans, and today we call them Palaeolithic art. Colour and form are the principal elements of this art, but because of the lost context, we are unable to understand completely what they meant to ice age artists.
Keywords: archaeology; arheologija; paleolitik; ledena doba; prazgodovinska umetnost; risanje; živali; barve; oblika; simbolika